Monomeric Immunoglobulin A from Plasma Inhibits Human Th17 Responses In Vitro Independent of FcαRI and DC-SIGN - Saha, Chaitrali; Das, Mrinmoy; Patil, Veerupaxagouda; Stephen-Victor, Emmanuel; Sharma, Meenu; Wymann, Sandra; Jordi, Monika; Vonarburg, Cédric; Kaveri, Srini V.; Bayry, Jagadeesh (Frontiers in Immunology, 2017)
Circulating immunoglobulins including IgG and IgM play a critical role in the immune homeostasis by modulating functions of immune cells. These functions are mediated in part by natural antibodies. However, despite being second most abundant antibody in the circulation, the immunoregulatory function of IgA is relatively unexplored. As Th17 cells are the key mediators of a variety of autoimmune, inflammatory and allergic diseases, we investigated the ability of monomeric IgA (mIgA) isolated from pooled plasma of healthy donors to modulate human Th17 cells. We show that mIgA inhibits differentiation and amplification of human Th17 cells and the production of their effector cytokine IL-17A. mIgA also suppresses IFN-γ responses under these experimental conditions. Suppressive effect of mIgA on Th17 responses is associated with reciprocal expansion of FoxP3-positive regulatory T cells. The effect of mIgA on Th17 cells is dependent on F(ab’)2 fragments and independent of FcαRI (CD89) and DC-SIGN. Mechanistically, the modulatory effect of mIgA on Th17 cells implicates suppression of phosphorylation of STAT3. Furthermore, mIgA binds to CD4+ T cells and recognizes the receptors for cytokines (IL-6Rα and IL-1RI) that mediate Th17 responses in a dose-dependent manner. Our findings thus reveal novel anti-inflammatory functions of IgA and suggest potential therapeutic utility of mIgA in autoimmune and inflammatory diseases that implicate Th17 cells.